The Impact of Parental Leadership on Organizational Commitment of those Working in the Iraqi Ministry of Higher Education and Scientific Research: The Intermediary Role of Ethical Climate - Alhamdany , Saba Noori (International Journal of Psychosocial Rehabilitation, 2020)
Parental leadership is one of the important strategies to improve the level of organizational commitment among employees, as well as to provide a suitable ethical climate for employees to help them face and overcome ethical dilemmas. The study aimed at exploring the impact of parental leadership on the level of organizational commitment of those working at the Iraqi Ministry of Higher Education and Scientific Research in the light of the presence of the ethical climate as an intermediary variable, To achieve the goal of the study, the Leader-Member Exchange Theory was used and a random class sample was taken, represented by the employees in the center of the ministry with the total sampling being (1000) employees. A 200 questionnaire copies were distributed which makes (20%) of the Ministry center from which the research sample was selected. The study led to the conclusion that the parental leadership, positively and with a statistical significance, affects both the organizational commitment and the ethical climate. The study also proved the partial intermediary role played by the ethical climate in the relationship between the parental leadership and the organizational commitment of employees working for the Ministry of Higher Education and Scientific Research, which in turn helps in improving the performance of those employees as well as in unveiling of all the gaps that may lead to a decrease in the level of ethical climate as well as in reducing the development level of the employees’ organizational commitment.